Mid-Infrared, Ultra-Broadband, Low-Loss, Compact Arbitrary Power Splitter Based on Adiabatic Mode Evolution - Jia Xu Brian Sia; Wanjun Wang; Xin Guo; Jin Zhou; Zecen Zhang; Mohamed Said Rouifed; Xiang Li; Zhong Liang Qiao; Chong Yang Liu; Callum Littlejohns; Graham T. Reed; Hong Wang (IEEE Photonics Journal)
We designed and demonstrated TE-mode arbitrary power splitters based on adiabatic mode evolution. The power splitters are designed with a footprint of smaller than 12 × 2.9 μm2, fabricated on a 400-nm silicon-on-insulator platform, requiring only a single etch step. The optimization process and the conditions for arbitrary-power splitting are performed using three-dimensional-FDTD simulations. We prove this concept through the fabrication of asymmetrical adiabatic evolution-based power splitters with splitting ratios of 50:50, 60:40, and 70:30. The fabricated devices are shown to agree closely with simulation results. Broadband operation with low insertion loss of 0.11–0.6 dB is demonstrated across the 3.66–3.89 μm wavelength range (230 nm). This component has applications in a multitude of areas such as spectroscopic optical sensing and optical phased arrays photonic integrated circuits etc.